A Critical Review on the Book Population Aging and the Generational Economy: A Global Perspective - Hatam Hosseini (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Population aging will be the inevitable demographic destiny of contemporary societies. Paying less attention to this phenomenon can make its consequences far more complex and difficult. One of the main ways to gain understanding and management of this phenomenon is by writing and translating scientific texts in this field. This paper aims to review and evaluate the book entitled “Population Aging and the Generational Economy: A Global Perspective”. This work is one of the few books in the field of population aging that has been published in Persian. It is reviewed from formal, structural, and content perspectives. The review revealed that despite formal, structural, and content shortcomings, the book is of suitable and desirable quality. Considering the changes in the age structure of the population of Iran, the Persian translation of this book cannot only be a good source for demography students, but also it can be used by demographers, economists, and population policymakers. It is suggested that in later editions, in addition to revising the text in terms of typographical and grammatical errors, the rationale for the selection of only nine chapters of the original text for the translation is explained by the translators in a brief introductory part.